FEATURES OF THE ACID-FORMING FUNCTION OF THE STOMACH IN DUODENAL ULCER IN CHILDREN - Ibatova Sh. M.; Ruzikulov N. E. (American Journals Publishing, 2024)
According to the materials of foreign and domestic statistical studies, duodenal ulcer (duodenal ulcer) in children accounts for 81% of all cases of the disease, gastric ulcer is observed in 13% of cases, and combined localization - in 6% of cases. 30 children with duodenal ulcer aged 7-15 years were examined. The examined children were divided into two main groups: group 1 included 12 patients with duodenal ulcer during an exacerbation, group 2 included 8 patients with duodenal ulcer without exacerbation, and the control group included 10 children hospitalized with functional dyspepsia. An increase in acid-forming function was observed in two main groups, while it was significantly higher in the group of children with duodenal ulcer during the exacerbation period.
Keywords: Patients, duodenal ulcer, Helicobacter pylori, acid-forming function of the stomach.